Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd003600
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the home environment for the reduction of injuries

Abstract: Analysis 1.1. Comparison 1 Multifactorial fall prevention intervention including: home hazard assessment and modification; medication review, bone and health assessment and exercise program, versus control, Outcome 1 Falls.. . .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 47 publications
(7 reference statements)
2
59
0
2
Order By: Relevance
“…Interventions promoting safe storage of household and other products. Interventions promoting the safe storage of household and other products (defined as use of safety catches or locks on cupboards/drawers, use of CRCs, and storage out of reach of children), were reported in 24 primary studies included in 11 reviews (DiGuiseppi & Roberts, 2000;Elkan et al, 2000;Guyer et al, 2009;Kendrick, Barlow et al, 2007;Kendrick, Coupland et al, 2007;Lyons et al, 2006;Lyons et al, 2003;Pearson et al, 2009;Towner et al, 1996United States Preventive Services Task Force, 1996) and in a further 7 studies not included in any reviews (Bulzacchelli et al, 2009;Gielen et al, 2007;LeBlanc et al, 2006;Nansel et al, 2008;Phelan et al, 2011;Reich et al, 2011;Swart et al, 2008) (see Table 4). One meta-analysis (Kendrick, Coupland et al, 2007) found evidence that education, with or without the provision of safety equipment was effective in increasing safe storage of household products (OR 1.63, 95% CI 1.22À2.17).…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Interventions promoting safe storage of household and other products. Interventions promoting the safe storage of household and other products (defined as use of safety catches or locks on cupboards/drawers, use of CRCs, and storage out of reach of children), were reported in 24 primary studies included in 11 reviews (DiGuiseppi & Roberts, 2000;Elkan et al, 2000;Guyer et al, 2009;Kendrick, Barlow et al, 2007;Kendrick, Coupland et al, 2007;Lyons et al, 2006;Lyons et al, 2003;Pearson et al, 2009;Towner et al, 1996United States Preventive Services Task Force, 1996) and in a further 7 studies not included in any reviews (Bulzacchelli et al, 2009;Gielen et al, 2007;LeBlanc et al, 2006;Nansel et al, 2008;Phelan et al, 2011;Reich et al, 2011;Swart et al, 2008) (see Table 4). One meta-analysis (Kendrick, Coupland et al, 2007) found evidence that education, with or without the provision of safety equipment was effective in increasing safe storage of household products (OR 1.63, 95% CI 1.22À2.17).…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
“…Interventions promoting the use of child resistant containers (CRCs) were reported from two studies (see Table 4) included in six reviews (Elkan et al, 2000;Kendrick, Coupland et al, 2007;Lyons et al, 2006;Lyons et al, 2003;Pearson et al, 2009;Towner et al, 1996) and a further two studies not included in reviews. One RCT evaluating the effects of home visits providing safety education, home safety inspection, and provision of child proof locks and child resistant caps (CRCs) reported significantly more intervention group families stored paraffin in containers with CRCs (OR 3.39, 95% CI 1.28À9.02) (Swart et al, 2008).…”
Section: Interventions Promoting Use Of Child Resistantmentioning
confidence: 99%
See 2 more Smart Citations
“…Os estudos que enfocaram a prioridade na intervenção ambiental não tiveram sucesso na demonstração conclusiva de seu poder de intervenção, especialmente por utilizarem como parâmetro a ocorrência prévia de acidentes 76 . As comunidades em crescimento possuem dificuldade de incentivar atividades de proteção contra injúrias, mas não há correlação estabelecida entre as diferenças nas características dos municípios e sua capacidade de desenvolver proteção física 77 .…”
Section: Escorpionismounclassified